2002
DOI: 10.1086/340027
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Human Immunodeficiency Virus Replication during Acute Measles

Abstract: To determine the effect of measles virus coinfection on plasma human immunodeficiency virus (HIV) RNA levels, a prospective study of hospitalized children with measles was conducted between January 1998 and October 2000 in Lusaka, Zambia. Plasma HIV RNA levels were measured during acute measles and 1 month after hospital discharge. The median plasma HIV RNA level in 33 children with measles who were followed longitudinally was 5339 copies/mL at study entry, 60,121 copies/mL at hospital discharge, and 387,148 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 67 publications
4
50
0
Order By: Relevance
“…Recently, measles infection has been shown to suppress HIV viremia in patients, 10 and we have also demonstrated that malaria parasites may suppress HIV-1 infec- tion in vitro. 11 Further studies are required for better understanding of interaction between these microbes and HIV-1 in co-infected patients.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, measles infection has been shown to suppress HIV viremia in patients, 10 and we have also demonstrated that malaria parasites may suppress HIV-1 infec- tion in vitro. 11 Further studies are required for better understanding of interaction between these microbes and HIV-1 in co-infected patients.…”
Section: Discussionsupporting
confidence: 51%
“…HIV-positive people with acute dengue or measles viruses infection have marked reductions in plasma HIV RNA concentration, suggesting viral interference (44,45). Although measles viruses has been shown to inhibit HIV replication independent of chemokines in vitro (46), several members of the Flavivirus family (HCV, Japanese Encephalitis Virus and Dengue Virus) alter the cellular release of cytokines and chemokines (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Some persons who are simultaneously infected with HIV-1 and either dengue, Orienta tsutsugamushi, hepatitis G/GB virus C, or measles morbilli virus have reduced viral loads compared with patients who are infected with HIV-1 alone or with HIV-1 and other pathogens. [17][18][19][20][21][22][23][24][25] In the case of hepatitis G virus (HGV), the mechanism of action is postulated to be via binding of the serum HGV E2 protein to CD81, leading to increased regulated on activation normal T expressed and secreted protein (RANTES) secretion and reduced CCR5 expression. 24 In vitro studies have shown that HTLV-type 2 infection might up-regulate the production of macrophage inflammatory protein-1␣ (MIP-1␣).…”
Section: Introductionmentioning
confidence: 99%